Integrated Framework for Measuring the Impact of Corporate Sustainability Performance on Financial Performance via Customer Attraction - Emmanuel Obinali Obioha; Heinz Eckart Klingelhöfer (Indonesian Journal of Sustainability Accounting and Management, 2023)
The study aims to develop an integrated framework for measuring the impact of corporate sustainability performance on financial performance via customer attraction. The study explores and communicates by literature the linkages and factors affecting corporate sustainability performance (i.e. socio-economic and environmental activities): how do proper socio-economic and environmental management translate to corporate socio-economic and environmental performances; how can factors of socio-economic performance (e.g. socio-economic development and human rights) and environmental performance (e.g. environmental process and product focus) translate via customer attraction to different measures of profit. The results prove that socio-economic development, human rights, environmental process, and product focus translate to corporate socio-economic environmental performance, and then – via customer attraction – positively influence financial performance. The study assists management to know how to achieve competitive advantage and increase their triple bottom lines by attracting and retaining customers, thus, how it ultimately influences environmental, social, and economic success. The value of the study is that it delivers an integrated framework for measuring the impact of corporate sustainability performance on financial performance via customer attraction.